EKSPEKTASI ORANG TUA TERHADAP PENDIDIKAN ANAK DALAM PERSPEKTIF PENDIDIKAN EKONOMI INFORMAL - Muhammad Hasan; Yani M; Tuti Supatminingsih; Inanna Inanna; Muhammad Dinar (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
AbstractThis study aims to determine parents' expectations of children's education in the perspective of economic education in Beroanging Village, West Bangkala District, Jeneponto Regency, South Sulawesi Province. This study is a qualitative study with a phenomenological approach. The informants in this study were parents who had school-age children at the elementary, junior high, high school, and university levels which were determined purposively based on the criteria of parents who had a high level of economic status but low education, parents who had a high level of education, and elderly who have a low level of education and social status. The results of this study indicate that parents' expectations of children's education in the perspective of economic education in Beroanging Village are divided into three, namely the expectations of parents who consider education as an investment are parents who have a low level of education but a high level of economic status, expectations of education as an economic good or consumption are parents who have a low level of education and economic status, and the expectation of education as a consumption good as well as an investment is parents with a high level of education.Keywords: Ekspektasi Orang Tua, Pendidikan Anak, Pendidikan Ekonomi Informal